Examining the Challenges Faced by Women Employees in Tourism Industry in Kabale District. - Kamugisha, Serestine (Kabale University, 2024)
The study examined the challenges faced by women employees in the tourism industry in Kabale District. The study was guided by three objectives which were: to identify the roles of women employees in the tourism industry, to establish the challenges women employees are facing in the tourism industry in Kabale district, to suggest the measures to solve the challenges women employees are facing in tourism industry in Kabale district. A targeted population was fifty-six (56) respondents who were considered for the study. These included senior staff, Head Guide, Manager, Tourists, Community members Local government officials. Both simple random and purposive sampling techniques in identifying the study sample population. The methods that were used in data collection included surveys, observation, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. According to the findings, 100% of the respondents agreed that there were several roles of women employees in the tourism industry including: women are better at anticipating guests' requirements, and their feminine touch gives beauty and elegance to the hospitality, women reduce gender inequality in development, women can play a role in regional dances, agriculture, homestays, food and beverage services, and making souvenirs, women are the key to tourism sustainability as the key in disseminating knowledge about cultural values, women play a role in making family decisions to do jobs, the process of involving women in tourism is shaped by gender ideology in society. The study revealed the challenges women employees are facing in the tourism industry and these included gender inequality in the hospitality industry, employers struggle when recruiting females into senior management positions, women having fewer opportunities to advance in their careers or to be promoted to a more senior position, women who have husbands and families are confronted. From objective three, the study indicated measures to solve the challenges women employees are facing in the tourism industry in Kabale district including regular training of the new workforce (female) on a regular basis is the only remedy available, need to create a more inclusive and equitable work environment, anti-discrimination policies, leadership and management training, flexible work arrangements, diversity and Inclusion Initiatives, education and skill development.